Movie watching as visual literacy attainment - Sakanti, Dinara Pinasti; Widodo, Pratomo (LingTera, 2020)
Most students view the movie as entertainment so they cannot enhance their English learning. In fact, the movie can be one of the effective visual literacy media to learn English. Thus, this research is aimed to investigate students' perception of the visual of the movie as visual-literacy media to support English language learning. The respondents were chosen through the purposive sampling technique. These respondents who have an interest in movies and have their basis in English language skill were chosen by the researcher. This research then was carried out at Universitas Islam Indonesia Yogyakarta. This research is conducted in a qualitative method in an informal setting. The result of this research is that the visual movie mostly in the process may boost student's affection rather than their cognitive so it does not quite support the actual language learning process. Moreover, this research is concluded that the use of movie may prefer entertainment daily. In terms of education, it may be different as the educator should highlight some instructions or topics first before the movie that is used for learning media is played. Furthermore, it is subjective to see student's perceptions even public toward the movie itself, whether it is only for entertainment or it could be appropriate for education as one of the visual literacy media.